2023
DOI: 10.3389/fcimb.2023.1061937
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of NS2B/NS3 protease inhibitors biomarker in curbing dengue virus infections: In silico vs. In vitro approach

Abstract: An increase in the occurrence of viral infectious diseases is a global concern for human health. According to a WHO report, dengue virus (DENV) is one of the most common viral diseases affecting approximately 400 million people annually, with worsening symptoms in nearly 1% of cases. Both academic and industrial researchers have conducted numerous studies on viral epidemiology, virus structure and function, source and route of infection, treatment targets, vaccines, and drugs. The development of CYD-TDV or Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 101 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it is suggested that having more interaction with the residue will lead to a better result in the inhibitory activity. Furthermore, to create the stable energy-favored ligands at the interface of a protein structure and alter the binding affinity for the drug efficacy, it was crucial to observe the hydrogen bonding and optimize the hydrophobic interactions [ 48 ]. It was found that both 3e and 3k showed more hydrogen bonding interactions with NS2B-NS3pro compared to quercetin ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is suggested that having more interaction with the residue will lead to a better result in the inhibitory activity. Furthermore, to create the stable energy-favored ligands at the interface of a protein structure and alter the binding affinity for the drug efficacy, it was crucial to observe the hydrogen bonding and optimize the hydrophobic interactions [ 48 ]. It was found that both 3e and 3k showed more hydrogen bonding interactions with NS2B-NS3pro compared to quercetin ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the level of viremia in dengue patients corresponds to the severity of the disease [ 5 , 11 ]. The viremia level was higher in secondary dengue infection, which may prolong the disease and increase the chances of manifesting severe dengue symptoms [ 5 , 11 , 12 , 13 , 14 ]. Treatments such as antivirals to reduce the level of viremia, hence, could possibly reduce the severity of dengue.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies are being explored to hinder the replication of the dengue virus, including targeting the NS3 protease, NS5 polymerase, and virus entry process. The NS3 protease plays a vital role in viral replication, and inhibiting this enzyme could disrupt the virus’s life cycle [ 10 , 12 , 13 , 14 ]. Several compounds have demonstrated promise in inhibiting the NS3 protease during preclinical studies [ 10 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytochemicals including fatty acids, glucosides, terpenes, flavonoids, phenolics, chalcones, acetamides, and peptides have shown potential as inhibitors of DENV, with curcumin, quercetin, and myricetin acting as noncompetitive inhibitors of the NS2b-NS3 protease enzyme [9]. In silico and in vitro studies have provided ample phytochemical hits for the experimental assessment of their use as DENV protease inhibitors [10], indicating that natural product derivatives can be designed and synthesized to enhance specificity and efficacy toward these proteases.…”
Section: Introductionmentioning
confidence: 99%